2001
DOI: 10.1029/2000wr900351
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic capture zone delineation within the generalized likelihood uncertainty estimation methodology: Conditioning on head observations

Abstract: Abstract. A stochastic methodology to evaluate the predictive uncertainty in well capture zones in heterogeneous aquifers with uncertain parameters is presented. The approach is based on the generalized likelihood uncertainty estimation methodology. The hydraulic conductivity is modeled as a random space function allowing for the uncertainty that stems from the imperfect knowledge of the parameters of the correlation structure. Parameters are sampled from prior distributions and are used for the generation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 39 publications
2
78
0
Order By: Relevance
“…In distributed groundwater modelling, this type of model evaluation suggests that equifinality is endemic to the problem (see Feyen et al, 2001;Binley and Beven, 2003). Similarly, in rainfall-runoff modelling, the use of distributed observational information (disappointingly) does not appear to help much in eliminating the equifinality problem (see Lamb et al, 1998;Blazkova et al, 2002;Blazkova and Beven, 2003;Christiaens and Feyen, 2002).…”
Section: Set Theoretic Methods For Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…In distributed groundwater modelling, this type of model evaluation suggests that equifinality is endemic to the problem (see Feyen et al, 2001;Binley and Beven, 2003). Similarly, in rainfall-runoff modelling, the use of distributed observational information (disappointingly) does not appear to help much in eliminating the equifinality problem (see Lamb et al, 1998;Blazkova et al, 2002;Blazkova and Beven, 2003;Christiaens and Feyen, 2002).…”
Section: Set Theoretic Methods For Model Evaluationmentioning
confidence: 99%
“…In part, the origins of this concept lie in purely empirical studies that have found many models giving good fits to data (e.g. Figure 1; for other recent examples in different areas of environmental modelling see Zak et al, 1999;Brazier at al., 2000;Beven and Freer, 2001a,b;Feyen et al, 2001;Mwakalila et al, 2001;Blazkova et al, 2002;Blazkova and Beven, 2002;Christiaens and Feyen, 2002;Freer et al, 2002;Martinez-Vilalta et al, 2002;Schulz and Beven, 2003). …”
Section: Introductionmentioning
confidence: 99%
“…Rojas et al, 2008Rojas et al, , 2009c, subjectively chosen threshold limits (e.g. Feyen et al, 2001) or set as a minimum level of performance (e.g. Binley and Beven, 2003).…”
Section: Multi-model Approach To Account For Conceptual Model and Scementioning
confidence: 99%
“…An informal likelihood measure is used to avoid over conditioning and exclude parts of the model (parameter) space that might provide acceptable fits to the data and be useful in prediction. Since its introduction in 1992, GLUE has found widespread application for uncertainty assessment in many fields of study, including modeling of the rainfallrunoff transformation (Beven and Binley, 1992;Freer et al, 1996;Lamb et al, 1998), soil erosion (Brazier et al, 2001), tracer dispersion in a river reach (Hankin et al, 2001), groundwater and well capture zone delineation (Feyen et al, 2001;Jensen, 2003), unsaturated zone (Mertens et al, 2004), flood inundation (Romanowicz et al, 1996;Aronica et al, 2002), land-surface-atmosphere interactions (Franks et al, 1997), soil freezing and thawing (Hanson and Lundin, 2006), crop yields and soil organic carbon (Wang et al, 2005), and ground radar-rainfall estimation (Tadesse and Anagnostou, 2005). Applications of GLUE are also found in distributed hydrologic modeling (McMichael et al, 2006;Muleta and Nicklow, 2005).…”
Section: Introductionmentioning
confidence: 99%